2013
DOI: 10.7224/1537-2073.2012-049
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Actionable Bladder Symptom Screening Tool for Multiple Sclerosis Patients

Abstract: Bladder symptoms such as urinary urgency, frequency, and incontinence are common in people with multiple sclerosis (MS). These symptoms, which often result from neurogenic detrusor overactivity (NDO), can have a major impact on patients' day-to-day lives. However, in many cases they are over-looked in the clinical management of MS. The objective of this study was to develop and validate a reliable, sensitive, and specific screening tool for patients with bladder problems related to MS. We performed a literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 17 publications
2
64
0
Order By: Relevance
“…The ABSST is an eight‐item questionnaire plus a final “Yes/No” item asking patients if they would like to receive help for their bladder problems, see Appendix S1. The total ABSST score ranges from 0 to 8 with a score of 3 or higher validated previously to indicate need for further urological evaluation/referral . Participants with an ABSST score ≥3 and/or who answered “yes” to the independent question “Do you want help for your bladder problems?” were given information about urology follow‐up with an outside urologist or with a urologist on staff at the MS Comprehensive Care Center.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ABSST is an eight‐item questionnaire plus a final “Yes/No” item asking patients if they would like to receive help for their bladder problems, see Appendix S1. The total ABSST score ranges from 0 to 8 with a score of 3 or higher validated previously to indicate need for further urological evaluation/referral . Participants with an ABSST score ≥3 and/or who answered “yes” to the independent question “Do you want help for your bladder problems?” were given information about urology follow‐up with an outside urologist or with a urologist on staff at the MS Comprehensive Care Center.…”
Section: Methodsmentioning
confidence: 99%
“…The Actionable Bladder Symptom and Screening Tool (ABSST) is a validated questionnaire that was developed to allow clinicians to identify patients with MS in need of urologic referral for bladder symptoms . A short form of the ABSST was also validated in this population to predict appropriate urological referral .…”
Section: Introductionmentioning
confidence: 99%
“…Litwiller et al 1 showed that even asymptomatic MS patients can suffer from LUTS. This has led a few groups to develop specific screening questionnaires, 15,21 while others based their profiling on combination of patients' properties with different test results. 18,20 Table 2 lists the recommendations made for different screening criteria.…”
Section: Evaluating Luts In Ms Patientsmentioning
confidence: 99%
“…Critical analysis of different guidelines [15][16][17][18][19][20][21] has resulted in dividing MS-related LUTS evaluation into basic and advanced testing.…”
Section: Evaluating Luts In Ms Patientsmentioning
confidence: 99%
“…Although there are numerous validated tools available to assess generalized urinary symptoms in neurogenic bladder patients [10], there are two validated questionnaires which are more specific to urinary symptoms in MS patients. The Actionable Bladder Symptom and Screening Tool is a good initial screening tool and helps primary care physicians identify MS patients with symptomatic UI who may benefit from initial treatment or referral to a urologist [11]. Similarly, the Neurogenic Bladder Symptom Score is a patient reported outcome measure that assesses impact of neurogenic detrusor overactivity [12].…”
Section: Diagnosticsmentioning
confidence: 99%